Evaluación técnico financiera del impacto de la remoción del daño de formación en pozos productores de dos Campos de la formación caballos en la cuenca del Putumayo (2019)
The present work is based on the technical and financial evaluation of the impact of the theoretical removal of the formation damage, for which a Microsoft Excel Macro was generated which allows, in a graphic way, the easy identification of the IPR curves before and after the removal of the types of formation damage present in the producing wells of the A and L fields in the Putumayo basin. This is due to the fact that currently the wells have presented a fall in oil production due to the reduction of permeability in the formation face caused by the types of damage found in each one.